Information Security and Privacy 20th Australasian Conference, ACISP 2015, Brisbane, QLD, Australia, June 29 -- July 1, 2015, Proceedings - Foo, Ernest; Stebila, Douglas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed conference proceedings of the 20th Australasian Conference on Information Security and Privacy, ACISP 2015, held in Brisbane, QLD, Australia, in June/July 2015. The 28 revised full papers presented in this volume were carefully revised and selected from 112 submissions. The papers are organized in topical sections on symmetric cryptanalysis; public key cryptography; identity-based encryption; digital signatures; security protocols; privacy protocols; symmetric constructions; homomorphic encryption and obfuscation.
Symmetric cryptanalysis -- Public key cryptography -- Identity-based encryption -- Digital signatures -- Security protocols -- Privacy protocols -- Symmetric constructions -- Homomorphic encryption and obfuscation.
Keywords: Computer science; Computer security; Data encryption (Computer science).; Algorithms; Management information systems; Computer Science; Systems and Data Security; Data Encryption; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Electronic books